2004
DOI: 10.1037/0893-3200.18.1.237
|View full text |Cite
|
Sign up to set email alerts
|

What Gets Dad Involved? A Longitudinal Study of Change in Parental Child Caregiving Involvement.

Abstract: Predictors of change in fathers' and mothers' perceptions of child caregiving involvement were examined. Middle-class 2-parent families (131 mothers and 98 fathers) with a target school-age child participated. Fathers and mothers completed annual questionnaires for 3 consecutive years. Latent growth curve modeling suggested that fathers were likely to increase their relative contribution to child caregiving over the course of 3 years when they had a greater proportion of male children in the family and when li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 34 publications
0
63
1
4
Order By: Relevance
“…In one of the few studies examining changes in parents' engagement in positive activities during children's infancy (at 3, 6, and 9 months old), Lang et al (2014) found that mothers and fathers increased their engagement with the child at similar growth rates. During middle childhood, fathers display increasing levels of global involvement while mothers display decreasing levels of global involvement (Wood & Repetti, 2004). The aforementioned studies suggest that parental engagement is subject to cross-time variations.…”
Section: Trends In Mothers' and Fathers' Engagementmentioning
confidence: 99%
See 4 more Smart Citations
“…In one of the few studies examining changes in parents' engagement in positive activities during children's infancy (at 3, 6, and 9 months old), Lang et al (2014) found that mothers and fathers increased their engagement with the child at similar growth rates. During middle childhood, fathers display increasing levels of global involvement while mothers display decreasing levels of global involvement (Wood & Repetti, 2004). The aforementioned studies suggest that parental engagement is subject to cross-time variations.…”
Section: Trends In Mothers' and Fathers' Engagementmentioning
confidence: 99%
“…Specifically, more studies are needed to further understand how mothers' and fathers' engagement in positive activities with the child is affected by the way parents balance their work and family roles. Moreover, longitudinal research on mothers' and fathers' engagement is still relatively scarce (Lang et al, 2014;Meteyer & Perry-Jenkins, 2010;Wood & Repetti, 2004). In one of the few studies examining changes in parents' engagement in positive activities during children's infancy (at 3, 6, and 9 months old), Lang et al (2014) found that mothers and fathers increased their engagement with the child at similar growth rates.…”
Section: Trends In Mothers' and Fathers' Engagementmentioning
confidence: 99%
See 3 more Smart Citations